2010
DOI: 10.2174/1874210601004010013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on the Gingival Crevicular Fluid Composition During Experimental Gingivitis. A Pilot Study

Abstract: Background:Cytokines have been proposed as potentially useful diagnostic or prognostic markers of periodontal inflammation related alterations during the experimental gingivitis model. The role of ageing in periodontal disease needs further elucidation; therefore investigations of its influence on host response are needed.Objective:To study the effect of age on interleukins IL -6, IL-8 and TNF-a levels in gingival crevicular fluid (GCF) and their correlations to clinical parameters during experimental gingivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
2
9
1
1
Order By: Relevance
“…At baseline, no significant differences were observed in the expression of any cytokine in GCF and PCF. This is in accordance with previous studies that showed that under healthy clinical conditions, the expression of biomarkers does not differ between implants and teeth (Tsalikis ; Salvi et al. ; Cionca et al.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…At baseline, no significant differences were observed in the expression of any cytokine in GCF and PCF. This is in accordance with previous studies that showed that under healthy clinical conditions, the expression of biomarkers does not differ between implants and teeth (Tsalikis ; Salvi et al. ; Cionca et al.…”
Section: Discussionsupporting
confidence: 93%
“…At baseline, no significant differences were observed in the expression of any cytokine in GCF and PCF. This is in accordance with previous studies that showed that under healthy clinical conditions, the expression of biomarkers does not differ between implants and teeth (Tsalikis 2010;Salvi et al 2012;Cionca et al 2016;Ramseier et al 2016). With the development of inflammation, significant changes were observed for several biomarkers assessed around implants and teeth that returned to baseline levels by the end of the experiment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A similar relationship between GCF cytokines and clinical gingival inflammation has been reported previously. 38,42 The application of any topical gel was not effective in reducing IL-1b levels to baseline levels in our study. At 29 days, IL-1b levels in GCF were significantly lower in the CRM and CHX-MTZ groups compared to the CHX group.…”
contrasting
confidence: 69%
“…Researchers have shown an increase in GCF volume after 21 days of no oral hygiene, but no such change was seen in our study. 38 The interventions might have controlled an increase. Smokers were excluded from this study due to the depressive effects of tobacco on gingival inflammation.…”
mentioning
confidence: 99%